Removal of Sr(II) ions from aqueous solution by human hair treated with EDTA - Fumihiko Ogata (2020)
© 2020 Elsevier Ltd Disposed human hair was treated with different concentrations of ethylenediamine-N,N,N′,N′-tetraacetic acid (EDTA) (10%, 25%, and 50% denoted as ED10, ED25, and ED50, respectively), and its Sr(II) adsorption capacity from the aqueous phase was evaluated. The amount of Sr(II) adsorbed onto ED25 was 17 mg/g. The amount of Sr(II) adsorbed using ED25 depended on the solution pH, and the optimal pH condition was approximately 4 in our experiment. Because the point of zero charge of human hair is approximately 3.67 to 3.70, electrostatic interaction between Sr(II) and human hair easily occurred. Finally, the Sr(II) adsorbed onto ED25 was easily desorbed using a sodium hydroxide solution at a pH of 3 (desorption percentage of 95.4%). EDTA treatment of human hair was useful for producing a novelty adsorbent to adsorb Sr(II) from aqueous solution. These results can be applied to the solution of problems regarding the water environment and waste materials.